Patterns of administrative practices for secondary school principals in the southern governorates of Palestine - Elyan, Heba Uqelan AbedAlAziz (Journal of Educational and Psychological Sciences, 2024)
The study aimed to identify the degree to which secondary school principals in the southern governorates practice administrative school patterns, From the teacher's point of view, the study used the decriptive analytical approach, and the study tool was a questionnaire that was distributed to a sample of (320) teacher in secondary schools in the Gaza strip, distributed among three districts (East_West_North). The results of the study were concluded as follows: The patterns of administrative practices among secondary school principals from the teacher's point of view came with an overall average of (3.84) alarge degree. As for the patterns level, the democratic style obtained the highest average of (3.93). Followed by the autocratic style with an average of (3.70), meaning they both received ahig rating, while the received ahig rating, while the permissive style received an average of (2.81) with amoderate rating. There are no statistically significant differences at the significance level between the average estimates of the study sample members regarding the degree to which secondary school principale practice parterns of administrative practices (Democratic_ Autocratic_Permissive) is attributed to the variables (service_gender_educational qualification_educational region) While there are statistically significant differences between the estimates of the averages of the members of the study sample due to the gender variable in the field of the democratic administrative style in favor of females. At the coclusion of the study the researcher made several recommendations, the most important of wich are: That the Ministry of Education hold recovery courses for them with the aim of providing them with everything new. Regular meetings are held determined by the director, in the presence of the director, teachers, and the parents council to review educational. Developments and problems related to students. The necessity of adopting an effective administrative style that pushes teachers to innovate and be creative by learning about distinguished administrative experiences.
Keywords: patterns of administrative practice; principals; secondary school; teachers